Morfometrik Ayam Sabung dalam Sistem Pemeliharaan Intensif - Amalia Nata; Cynthia D Gaina; Yohanes TRMR Simarmata (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2023)
This study aims to determine the morphometrics of the 3 age groups on the consumption of feed with the same nutrition as well as on growth. The material used is 50 male fighting cocks which have been separated based on 3 age categories, namely 6-8 months, 9-12 months, 13-30 months. The research method used in this research is descriptive analysis (mean, standard deviation, coefficient of variance and correlation test) and followed by t-test. Data were collected by direct observation and measurement of quantitative properties based on the observed parameters. The results of this study show a description of the qualitative and quantitative characteristics of male fighting cocks based on 3 age categories very diverse and have different characteristics ranging from eye color, feather color and shank color, then from the results of quantitative analysis of maxilla length, wing length, chest length , chest width, femur length, tibia length, shank length, third toe length and shank circumference, had different averages and correlated from high to medium. From the results of the t-test on feed and morphometrics, there were several significant differences that occurred between maxilla length, wing length, chest length, chest width, femur length, and shank circumference (P<0.05) while in tibia length, shank length, and the length of the third toe did not show a significant difference (P>0.05). Then the results of the t-test on the feed given to the body weight of fighting cocks there was a significant difference from the 1st week of feeding to the 6th week of feeding (P<0.05). Differences can occur due to several factors, namely the content of food substances in the feed, especially the energy and protein content, and can be influenced by environmental factors, genetics, maintenance management, drug administration, vitamins, herbal herbs and environmental temperature.